2005
DOI: 10.1007/s10695-005-2832-2
|View full text |Cite
|
Sign up to set email alerts
|

Pyridoxine deficiency of grouper, Epinephelus coioides: physiological and biochemical alteration

Abstract: Pyridoxine is essential for animals. The purpose of this study was to investigate the pyridoxine deficiency symptoms and the fit dose of pyridoxine to keep normal physiological function in grouper, Epinephelus coioides. Graded levels of pyridoxine (0, 1, 2, 4, 8, 16, 32 mg pyridoxine kg )1 diet) were fed to grouper juveniles (14.83±0.31 g) for 8 weeks, and then some physiological and biochemical parameters were measured. Pyridoxine deficiency symptoms such as anorexia, poor survival, convulsion, helically swim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…In other words, carbohydrate is not the most important source of energy in carnivorous fish (Wilson 1994), and once carbohydrate metabolism is impaired under extreme conditions (such as in thiamin deficiency), fish can still live for a relatively long time. Taking into account that our previous study (Huang et al 2005) found that grouper fish were very susceptible to pyridoxine deficiency, we suggest that our results emphasize the fact that carbohydrate is relatively less important than protein in carnivorous fish.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In other words, carbohydrate is not the most important source of energy in carnivorous fish (Wilson 1994), and once carbohydrate metabolism is impaired under extreme conditions (such as in thiamin deficiency), fish can still live for a relatively long time. Taking into account that our previous study (Huang et al 2005) found that grouper fish were very susceptible to pyridoxine deficiency, we suggest that our results emphasize the fact that carbohydrate is relatively less important than protein in carnivorous fish.…”
Section: Discussionsupporting
confidence: 70%
“…However, to date very little physiological research has focused on the role of thiamin in fish. In Asia, the grouper, Epinephelus coioides, is considered to be an important commercial maricultured carnivorous fish (Boonyaratpalin 1997), but very little information has been published on the role of the B-family vitamins in this fish; the exception being pyridoxine (Huang et al 2005). Our previous study (Huang et al 2005) reported that symptoms of pyridoxine deficiency in the grouper resemble those reported in mammals (Baxter 2003).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, most studies on oxidative stress in fish have focused on natural and anthropogenic toxicological aspects, such as intrinsic factors in the fish itself, environmental factors and xenobiotics (Winston and Di Giulio 1991). Recent research has begun to pay attention to the roles of nutrient factors in the antioxidant system of fish, and a few nutrients have been preliminarily studied, including energy diets such as protein (Lopez-Bote et al 2001), lipids (Alvarez et al 1998), fatty acids (Stéphan et al 1995) and digestible carbohydrate (Rueda-Jassoa et al 2004); vitamins such as vitamin E (George et al 2000), vitamin C (Dabrowski et al 2004), vitamin A (Fontagné et al 2006), pyridoxine (Huang et al 2005) and thiamin (Huang et al 2007); minerals such as selenium (Lin and Shiau 2005), iron (Andersen et al 1998) and zinc (Kucukbay et al 2006). However, little research (but see Woodward 1983) concerns the role of riboflavin in antioxidant defense systems in fish.…”
mentioning
confidence: 99%
“…Recently in our laboratory, some of the B-family vitamins, such as pyridoxine (Huang et al 2005) and thiamin (Huang et al 2007), have been studied concerning their physiological function as well as antioxidant role in this fish species. Therefore, as one of the studies among a series of research focusing on the physiological and biochemical function of the B-family vitamins in E. coioides, the aim of the present study was to provide more precise information concerning the effects of dietary riboflavin on antioxidant defense.…”
mentioning
confidence: 99%